A 14-Year Italian Experience in DM2 Genetic Testing: Frequency and Distribution of Normal and Premutated CNBP Alleles - Botta, Annalisa; Visconti, Virginia Veronica; Fontana, Luana; Bisceglia, Paola; Bengala, Mario; Massa, Roberto; Bagni, Ilaria; Cardani, Rosanna; Sangiuolo, Federica; Meola, Giovanni; Antonini, Giovanni; Petrucci, Antonio; et al. (Frontiers in Genetics, 2021)
Myotonic Dystrophy type 2 (DM2) is a multisystemic disorder caused by a [CCTG]n in intron 1 of CNBP gene. The CCTG repeat tract is part of a complex (TG)v(TCTG)w(CCTG)x(NCTG)y(CCTG)z motif generally interrupted in CNBP healthy range alleles. Here we report our 14-years experience of DM2 postnatal genetic testing in a total of 570 individuals. DM2 locus has been analyzed by a combination of SR-PCR, TP-PCR, LR-PCR and Sanger sequencing of CNBP alleles. DM2 molecular diagnosis has been confirmed in 187/570 samples analyzed (32.8 %) and is mainly associated with the presence of myotonia in patients. This set of CNBP alleles showed unimodal distribution with 25 different alleles ranging from 108 to 168 bp, in accordance with previous studies on European populations. The most frequent CNBP alleles consisted of 138, 134, 140 and 136 bps with an overall locus heterozigosity of 90%. Sequencing of 103 unexpanded CNBP alleles in DM2-positive patients, revealed that the (CCTG)5(NCTG)3(CCTG)7 and (CCTG)6(NCTG)3(CCTG)7 are the most common interruption motifs. We also characterized 5 CNBP premutated alleles with (CCTG)n repetitions from n=36 to n=53. However, the molecular and clinical consequences in our cohort of samples are not unequivocal. Data emerged from this study are representative of the Italian population and are useful tools for National and European centers offering DM2 genetic testing and counselling.